2011
DOI: 10.1002/mabi.201100029
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Characterization of an Electroactive Carbon‐Nanotube‐Based Nanofiber Scaffold for Tissue Engineering

Abstract: In an effort to reduce organ replacement and enhance tissue repair, there has been a tremendous effort to create biomechanically optimized scaffolds for tissue engineering applications. In contrast, the development and characterization of electroactive scaffolds has attracted little attention. Consequently, the creation and characterization of a carbon nanotube based poly(lactic acid) nanofiber scaffold is described herein. After 28 d in physiological solution at 37 °C, a change in the mass, chemical propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…Nanofibers are the most reported materials, ranging from synthetic biodegradable polymers [polylactic acid (PLA), 184 poly(D,L-lactic-co-glycolicacid)(PLGA), 185 polyvinyl alcohol (PVA) 186 or polycaprolactone (PCL)], to natural materials, including collagen, 187 gelatin 188 and chitosan. 189 In addition, nanotubes like carbon nanotubes (CNTs) 190 and titanium dioxide (TiO 2 ) nanotubes, are good candidates for scaffold fabrication (e.g., in bone replacement therapy), in view of their tremendous mechanical strengths.…”
Section: Applications In Tissue Engineering and Regenerative Medicinementioning
confidence: 99%
“…Nanofibers are the most reported materials, ranging from synthetic biodegradable polymers [polylactic acid (PLA), 184 poly(D,L-lactic-co-glycolicacid)(PLGA), 185 polyvinyl alcohol (PVA) 186 or polycaprolactone (PCL)], to natural materials, including collagen, 187 gelatin 188 and chitosan. 189 In addition, nanotubes like carbon nanotubes (CNTs) 190 and titanium dioxide (TiO 2 ) nanotubes, are good candidates for scaffold fabrication (e.g., in bone replacement therapy), in view of their tremendous mechanical strengths.…”
Section: Applications In Tissue Engineering and Regenerative Medicinementioning
confidence: 99%
“…Due to the ease of fabrication, carbon nano-fi bers and nanotubes have also been combined with polyhydroxyesters to produce composites with enhanced mechanical properties (Chrissafi s et al ., 2010 ;Mackle et al ., 2011 ) and improved degradation rates (Chrissafi s et al ., 2010 ). In vitro cell response studies to aligned carbon nanotube composites showed fi broblast morphology resembling that of native tissues (Yuen et al ., 2008 ).…”
Section: Composites For Engineered Ligament Scaffoldsmentioning
confidence: 99%
“…In vitro cell response studies to aligned carbon nanotube composites showed fi broblast morphology resembling that of native tissues (Yuen et al ., 2008 ). Although not much work has been done specifi cally for ACL regeneration, adequate biocompatibility has been shown in vitro with periodontal ligament cells (Mei et al ., 2007 ) and hMSCs (Mackle et al ., 2011 ) seeded on carbon nanocomposites. These results indicated that carbon nanocomposites should be further researched for ligament scaffold construction.…”
Section: Composites For Engineered Ligament Scaffoldsmentioning
confidence: 99%
“…Their unique electrical and mechanical properties can be exploited to create biomimetic tailored scaffolds. Initially, a range of MWCNTs concentrations were screened to determine the optimal electrical properties [9]. In recent years, the combination of natural and synthetic polymers with various other materials has shown improvement in their chemical, physical, and biological properties [5].…”
Section: Introductionmentioning
confidence: 99%